OUTCOMES OF PARS PLANA VITRECTOMY FOR MACULAR HOLE IN PATIENTS WITH UVEITIS. (September 2018) - Callaway, Natalia F.; Gonzalez, Marco A.; Yonekawa, Yoshihiro; Faia, Lisa J.; Mandelcorn, Efrem D.; Khurana, Rahul N.; Saleh, Mohamed G. A.; Lin, Phoebe; Sobrin, Lucia; Albini, Thomas A.
Abstract : Purpose: Inflammatory macular hole is a rare complication of uveitis, and data on surgical outcomes of closure are scarce. The purpose of this study is to evaluate the anatomical and visual outcomes of conventional pars plana vitrectomy for patients with uveitis. Methods: Noncomparative, interventional, and consecutive case series from 6 vitreoretinal surgical centers from 2007 to 2015. Twenty eyes of 19 patients were included with 4 patients separated as viral retinitis. The primary outcome was change in best-corrected visual acuity at Month 3. Secondary outcomes were closure of the macular hole and postoperative optical coherence tomography characteristics. Results: All eyes underwent conventional three-port pars plana vitrectomy with indocyanine green–assisted internal limiting membrane peeling. Mean Snellen best-corrected visual acuity improved from 20/200 to 20/63 ( P = 0.01 for a difference in logarithm of the minimum angle of resolution) at Month 3. Twelve (75%) of patients achieved 2 or more lines of visual acuity improvement by postoperative Month 3. Surgery resulted in decreased epiretinal membrane ( P = 0.002), intraretinal fluid ( P < 0.001), subretinal fluid ( P = 0.029), central subfield thickness ( P < 0.001), and central cube volume ( P = 0.041). Surgical intervention achieved anatomical success, as measured by macular hole closure, in 13 (81%) of patients at postoperative Month 3. Conclusion: Patients with inflammatory macular hole respond well to conventional surgery, with good anatomical and visual acuity outcomes. Abstract : Inflammatory macular hole is a rare complication of uveitis that can result in central vision loss. Few research studies exist on surgical outcomes of inflammatory macular hole. This multicenter study represents the largest case series of surgical outcomes for uveitic macular hole and reports improved anatomical and visual outcomes after surgical intervention.